2017
DOI: 10.1038/s41598-017-09907-6
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes from high glucose-treated glomerular endothelial cells trigger the epithelial-mesenchymal transition and dysfunction of podocytes

Abstract: New data indicate that abnormal glomerular endothelial cell (GEC)-podocyte crosstalk plays a critical role in diabetic nephropathy (DN). The aim of our study is to investigate the role of exosomes from high glucose (HG)-treated GECs in the epithelial-mesenchymal transition (EMT) and dysfunction of podocytes. In this study, exosomes were extracted from GEC culture supernatants and podocytes were incubated with the GEC-derived exosomes. Here, we demonstrate that HG induces the endothelial-mesenchymal transition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
128
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(136 citation statements)
references
References 42 publications
3
128
1
Order By: Relevance
“…Exosomes are the nanosized membrane-bound delivery vesicles, which play a critical role in regulating cellular biofunction by mediating cell-to-cell communication [31]. Exosomes extracted from HG-treated glomerular endothelial cells (GECs) can be internalized by podocytes, leading to podocyte EMT and renal fibrosis [32,33]. In contrast, some exosomes exert protective effects to be used for treatment of many diseases including podocyte injury and kidney disease.…”
Section: Discussionmentioning
confidence: 99%
“…Exosomes are the nanosized membrane-bound delivery vesicles, which play a critical role in regulating cellular biofunction by mediating cell-to-cell communication [31]. Exosomes extracted from HG-treated glomerular endothelial cells (GECs) can be internalized by podocytes, leading to podocyte EMT and renal fibrosis [32,33]. In contrast, some exosomes exert protective effects to be used for treatment of many diseases including podocyte injury and kidney disease.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the podocytes, which reside in the visceral layer of Bowman's capsule and form the final filtration barrier, are connected to the GBM by interdigitated foot processes that leave open only thin gaps, designated filtration slits, for filtration through the GBM. These slits, however, are coated by a diaphragm of filter proteins, such as podocin, nephrins, podocalyxin, and protocadherins, which further reduce the filtration surface [250,252]. Thus, glomerular filtration is highly selective: only molecular complexes below 6.4 nm in diameter and under 70 kDa may physiologically transit into the lumen of the nephron [253].…”
Section: Evs In Renal Pathophysiologymentioning
confidence: 99%
“…These endothelial EVs may vehiculate TGF-β1 mRNA, a key mediator of the epithelial-mesenchymal transition, whose translation activates myofibroblastic intracapsular proliferation and glomerular dysfunction. Thus, an EV-mediated endothelial-podocyte crosstalk contributes to glomerular fibrosis and loss of renal function in diabetic nephropathy [252].…”
Section: Evs In Renal Pathophysiologymentioning
confidence: 99%
“…Exosomes isolated from high-glucose-treated glomerular endothelial cells played a crosstalk role to activate EMT and fibrotic changes of mesangial cells and podocytes in DN. Wu et al, 2017) (Continued)…”
Section: Renal Tubular Epithelial Cells (Mouse)mentioning
confidence: 99%
“…A recent study has shown that type 1 DN was associated with increases in urinary excretion of exosomal plasmin, prostasin, and urokinase as well as the proteolytic activation of ENaC that might contribute to the dysfunction of Na + excretion and hypertension (Andersen et al, 2015). Interestingly, exosomes derived from high-glucose-treated glomerular endothelial cells played a crosstalk role to activate epithelial mesenchymal transition (EMT) and fibrotic changes of glomerular mesangial cells and podocytes in DN Wu et al, 2017). High-glucose also enhanced secretion of exosomes from macrophages, which then caused mesangial proliferation and activated inflammatory cascade in the renal tissue (Zhu et al, 2019b).…”
Section: Chronic Kidney Diseasementioning
confidence: 99%